Sustainable freight transport systems : opportunities for developing countries : note by the UNCTAD Secretariat (UN New YorkUS, 2015)
Highlights the potential for freight transport to emerge as an important sector that adheres to sustainable development principles and promotes people, prosperity, environment and sustainable partnerships.
Keywords: FREIGHT